Sex and age-related differences in athletes` health status in individual and team sports - Sindik, J.; Sarac, J.; Grgurinovic, T.; Tomic, D.; Pausek, D.; Missoni, S. (Croatian Sports Medicine Journal, 2016)
Main goal of this study was to determine the differences between the athletes who are actively engaged in team vs. individual sports, stratified by age groups and sex, in BMI (Body Mass Index) and other chosen biochemical health indicators. Second goal is directed on forecasting the criterium BMI, on the base of predictors (i.e. chosen morphological and biochemical health indicators, except body height and body mass), for the athletes from team and individual sports, separately for males and females and separately for different age groups. The data were collected during routine medical examinations performed by physicians from the Polyclinic for Occupational Health and Sport in Zagreb. The database comprised medical data obtained in 2011 and 2012 from 8482 athletes in the City of Zagreb. Collected data included height, body mass , BMI, blood pressure (diastolic and systolic), heart rate, hemoglobin, hematocrit, leukocytes, thrombocytes, and sedimentation rate. Inspecting the results, it could be concluded that more statistically significant differences in the variables in research, related to the sport type (team/individual), have been detected in male athletes (as compared with female ones). These differences are more emphasized in team than in the individual sports. More statistically significant predictors are found in males (than in females) and more in team sports. The results could be mainly discussed in terms of the differences among requests in different sports, different levels of professional sport training in certain sports, as well as in terms of sex differences in growth.